Pterygium treatment using 5-FU as adjuvant treatment compared to conjunctiva autograft (2008)
Background The use of conjunctiva autograft, adjunct antimetabolite therapy has been shown to be effective in preventing pterygium recurrence. Objective To compare 5 fluorouracil (5-FU) to conjunctival autograft in the treatment of large, fleshy pterygium. Methods A randomised controlled prospective study of outcome of pterygium treatment using 5-FU as adjuvant treatment compared to conjunctiva autograft. Thirty-five eyes with large pterygium treated with bare sclera conjunctival excision plus 5-FU were compared with 33 eyes treated with excision and conjunctival autograft alone. Results Post-operative pterygium recurrence was observed in four (11.4%) eyes treated with 5-FU and 4 (12.1%) eyes treated with conjunctiva autograft (P40.05). The post-operative complications included, granuloma formation 11.4% for 5-FU and 3.0% for autograft and conjunctival discharge 5.7% for 5-FU group only. Conclusion 5-FU is marginally superior to conjunctival autograft in the prevention of pterygium recurrence but neither gives a more desirable single digit recurrence rate. Randomised studies combining both conjunctival autograft and 5-FU in pterygium treatment is advocated to further explore their effect.